ANALISIS KELAYAKAN USAHA PRODUKSI SUDANG LEPET (Studi Kasus di Desa Sangsit, Kecamatan Sawan) - Widiani, Komang Widi; Satria, Gde Agung (Jurnal Daya Saing, 2023)
The purpose of this study was to determine the feasibility of the sudang lepet production business from the financial aspects analyzed, namely Payback Period (PP), Net Percent Value (NPV) and non-financial aspects, namely management aspects, marketing aspects, and production aspects.This research is a qualitative-quantitative descriptive research. The subject of this research is shrimp shrimp production entrepreneur in Sangsit Village and the object of this research is the feasibility of shrimp shrimp production business. The population of this research was eight entrepreneurs and theselection of research informants was carried out using a purposive sampling method and five entrepreneurs were obtained as research informants. Methods of data collection is done by nterviewing and documentation techniques.The results of this study indicate that: (1) Viewed from the financial aspect, the five sudang lepet production businesses are very feasible to run. (2) In terms of management aspects, it is stated that the five slow production businesses are very feasible to run. (3) Viewed from the marketing aspect, the five sudang lepet production businesses are very feasible to run. (4) Viewed from the production aspect, the five sudang lepet production businesses are very feasible to run